ANALISIS PERAN DAN STRATEGI KEPEMIMPINAN KOLABORATIF - Yeni Widyastuti (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
Collaborative Governance involving public and private stakeholders together in a forum to generate consensus in decision making. The purpose of stakeholders’ involvement is to formulate and implement policies. This cross-sectoral role contributes higher quality of public services. Role of the leadership is needed when the decision is made, in practice every stakeholders or actor involved has a clear task regarding who is responsible, what should they do and how to do technically. The leader act as a convener, demands the power of meeting including the ability to persuade stakeholders to participate, has experience and reputation of unbiased issued in question. Strategic leadership training and development become an important factor in collaborative governance. Keywords; Collaborative Governance. Leadership, Role, Strategy